Detection of skin neoplasia by fractal analysis of 2D images and microtopography - Costa, Manuel F. M. (2017)
Early detection of skin cancer is fundamental to its successful treatment. Changes in the shape, including the relief, of skin lesions are an indicator of a possible malignancy l and image processing optical microtopographic inspection of skin lesions can be used to identify diagnostic patterns of benign and malignant skin lesions. Statistical parameters like the mean roughness (Ra) may allow the discrimination between different types of lesions and degree of malignancy. Fractal analysis of bi-dimensional and 3D images of skin lesions can validate or complement this assessment by calculation of its fractal dimensions (FD). In the study reported herein, the microtopographic inspection of the skin lesions was performed by using the optical triangulation based microtopographer developed at the Physics Department of the University of Minho, MICROTOP.03.MFC. Images of the skin lesions were digitized and processed in order to calculate fractal parameters.